2016
DOI: 10.2500/ajra.2016.30.4271
|View full text |Cite
|
Sign up to set email alerts
|

Extensive versus Functional Endoscopic Sinus Surgery for Chronic Rhinosinusitis with Nasal Polyps and Asthma: A 1-year Study

Abstract: EESS for patients with CRSwNP and with asthma may help to improve the subjective olfaction and endoscopic appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 34 publications
1
65
0
Order By: Relevance
“…During follow‐up, significantly more patients within the CRSwNP cohort underwent endoscopy or had a CT scan versus the reference group (60.4% vs. 0.2% and 69.1% vs. 0.4, respectively; both P < .001), which correlates with the use of endoscopy and CT scans for clinical assessment and diagnosis of CRSwNP. In the US, FESS is widely considered the standard surgical intervention for CRSwNP, and in this study, 42.7% of patients with CRSwNP underwent FESS. A previous study of patients with CRS found that 46.2% underwent endoscopic sinus surgery; therefore, although our results were as expected, we believe that this is one of the first times such data have been reported in patients with CRSwNP specifically.…”
Section: Discussionmentioning
confidence: 84%
“…During follow‐up, significantly more patients within the CRSwNP cohort underwent endoscopy or had a CT scan versus the reference group (60.4% vs. 0.2% and 69.1% vs. 0.4, respectively; both P < .001), which correlates with the use of endoscopy and CT scans for clinical assessment and diagnosis of CRSwNP. In the US, FESS is widely considered the standard surgical intervention for CRSwNP, and in this study, 42.7% of patients with CRSwNP underwent FESS. A previous study of patients with CRS found that 46.2% underwent endoscopic sinus surgery; therefore, although our results were as expected, we believe that this is one of the first times such data have been reported in patients with CRSwNP specifically.…”
Section: Discussionmentioning
confidence: 84%
“…Philips et al [15] showed that the most common and also recoverable symptom after endoscopic sinus surgery is headache. Chen et al [13] found significant improvement in the VAS score at one year after surgery. Proimos et al [7] found statistically significant improvement after operation in nasal blockage, smell, facial pain and headache.…”
Section: Discussionmentioning
confidence: 95%
“…There is some evidence to support a more extensive approach, particularly in eosinophilic disease or CRSwNP (75,76) .…”
Section: Ii) Extent Of Surgerymentioning
confidence: 99%